Digital marketing strategic training in smes developed at the department of trade and industry of Bandung City - Rijayana, Iwan; Amalia, Endang; Hamdani, Dani; Chaniago, Muhammad Benny (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2023)
Digital marketing is used by many business people around the world, from small-scale SMEs to large ones. One of the solutions offered is digital marketing strategy training, which is an alternative for SMEs with limited promotional budgets. The use of social media such as Facebook, Instagram, and websites is an alternative that can be used to create a brand image and digital and social media presence for the customer journey through sales and marketing funnels. This research aims to get digital marketing strategy training for SMEs developed at the Bandung City Trade and Industry Service. With this training, community empowerment programs related to the implementation of digital marketing can run smoothly. The proposed activity plan begins with a preliminary survey and outreach, followed by the development, review, and delivery of training materials, as well as the training itself, as well as guidance and assistance, monitoring, and assessment. Publication is one of the required submissions. The qualitative descriptive research analysis method was used in this study. The results of the training show that business actors are very positive about this activity, which provides benefits and inspiration so that they have a follow-up plan to run their business online.